Exploring the Physical and Mental Health Challenges of Teenage Pregnancy: A Qualitative Study in the Tamale Metropolis, Ghana - Rafatu Tahiru; Comfort Kona; Abiba Nyari; Tawfik Mohammed; Dorothy Anukem Pwamang (Journal of Family and Reproductive Health)
Objective: Teenage pregnancy poses significant public health challenges globally, particularly affecting the physical and mental well-being of adolescent girls. Despite a global decline in teenage birth rates, regions like sub-Saharan Africa continue to experience high prevalence. In Ghana's Tamale metropolis, teenage pregnancy rates have shown a concerning rise, underscoring the need for an in-depth exploration of its multifaceted impacts. This study aims to explore the physical and mental health effects of teenage pregnancy in the Tamale metropolis, capturing their personal experiences and coping mechanisms. Materials and methods: Employing a qualitative exploratory descriptive design, the study conducted a focus group discussion with 10 first-time teenage mothers aged 13–19 whose babies were less than 1 month. Participants were purposively sampled from antenatal records across five Community-based Health Planning and Services (CHPS) compounds. Discussions, guided by the socioecological model, were transcribed, translated, and thematically analyzed using NVivo software. Results: Participants reported numerous physical health challenges, including severe nausea, vomiting, exhaustion, musculoskeletal pain, and infections like candidiasis. Mental health struggles encompass feelings of sadness, irritability, anxiety, and societal-induced stress. Coping strategies varied, with reliance on trusted individuals, avoidance of social situations, support from healthcare professionals, and family backing emerging as predominant themes. Conclusion: This study revealed profound physical and mental health challenges compounded by societal stigma and limited resources. Strengthening social support networks, reducing stigma, and promoting patient-centered care are imperative. Targeted interventions are also essential to enhance health outcomes for these young mothers and their children.